See food diet? Cultural differences in estimating fullness and intake as a function of plate size. (1st October 2017) - Peng, Mei; Adam, Sarah; Hautus, Michael J.; Shin, Myoungju; Duizer, Lisa M.; Yan, Huiquan
Abstract: Previous research has suggested that manipulations of plate size can have a direct impact on perception of food intake, measured by estimated fullness and intake. The present study, involving 570 individuals across Canada, China, Korea, and New Zealand, is the first empirical study to investigate cultural influences on perception of food portion as a function of plate size. The respondents viewed photographs of ten culturally diverse dishes presented on large (27 cm) and small (23 cm) plates, and then rated their estimated usual intake and expected fullness after consuming the dish, using 100-point visual analog scales. The data were analysed with a mixed-model ANCOVA controlling for individual BMI, liking and familiarity of the presented food. The results showed clear cultural differences: (1) manipulations of the plate size had no effect on the expected fullness or the estimated intake of the Chinese and Korean respondents, as opposed to significant effects in Canadians and New Zealanders ( p < 0.05); (2) Canadian (88.91 ± 0.42) and New Zealanders (90.37 ± 0.41) reported significantly higher estimated intake ratings than Chinese (80.80 ± 0.38) or Korean (81.69 ± 0.44; p < 0.05), notwithstanding the estimated fullness ratings from the Western respondents were comparable or even higher than those from the Asian respondents. Overall, these findings, from a cultural perspective, support the notion that estimation of fullness and intake are learned through dining experiences, and highlight the importance of considering eating environments and contexts when assessing individual behaviours relating to food intake.